Regional information & communication services and technologies profile (including telecommunications) : the continuing efforts of the Caribbean Community (CARICOM) : agenda 2003 - Wiltshire Forde, Jacqueline (CCS GeorgetownGY, 2002)
Focuses on the regional framework approach in order to maximise benefits of ICT development. Looks at progress to date. Highlights CARICOM's agenda 2003 with its agreed activities. Notes the CARICOM Secretariat's ICT internal and external strategy.